2013
DOI: 10.2903/sp.efsa.2013.en-440
|View full text |Cite
|
Sign up to set email alerts
|

Review of substances/agents that have direct beneficial effect on the environment: mode of action and assessment of efficacy

Abstract: Some substances and agents, used as livestock feed additives, could have an important role to play in delivering sustainable increases in productivity and simultaneous reductions in damaging pollutants. This research project aimed to identify livestock feed additives which may have potential benefits for the environment and create an inventory of these which included other relevant scientific and descriptive data. This is the final report of the project. It provides a detailed description of the methodology us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 102 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Among 246 nutritional substances or agents that could potentially reduce GHG emissions in the environment by livestock, Lewis et al (2013) reviewed that 130 substances offer potential benefits. For non-ruminants, specific feed additives or ingredients containing specific functional compounds, such as probiotics, plant metabolites and organic acids have been studied and could be further investigated as mitigation strategies to reduce enteric methane formation in pigs.…”
Section: Influence Of Feed Additives and Specific Ingredientsmentioning
confidence: 99%
“…Among 246 nutritional substances or agents that could potentially reduce GHG emissions in the environment by livestock, Lewis et al (2013) reviewed that 130 substances offer potential benefits. For non-ruminants, specific feed additives or ingredients containing specific functional compounds, such as probiotics, plant metabolites and organic acids have been studied and could be further investigated as mitigation strategies to reduce enteric methane formation in pigs.…”
Section: Influence Of Feed Additives and Specific Ingredientsmentioning
confidence: 99%
“…Feed additives for improved N-use efficiency and lower N ex in farm manure or lower NH 3 formation due to urease inhibitors, e.g., benzoic acid, are described, for instance, in [105,106]. According to these studies, pigs have the second highest mitigation potential regarding feed additives, following cattle.…”
Section: Use Of Feed Additivesmentioning
confidence: 99%
“…However, contradictory results can be found in the literature. For example, one study reported an average of −23% NH 3 emissions from the addition of benzoic acid, with a high variation of between +116% and −71% [105], whereas another study confirmed highly effective mitigation effects of CP reduction in finishing pigs but reported no significant effect of adding 1% benzoic acid to the diet [101].…”
Section: Use Of Feed Additivesmentioning
confidence: 99%
“…With the application of essential oil, the methanogenesis decreases especially by reducing microbial populations [160]. The Allium arenarium oil (garlic oil), a highly promising essential oil, was significantly reduced methane production both in-vivo and in-vitro by 12% and 36%, respectively [161].…”
Section: Introductionmentioning
confidence: 99%